2007
DOI: 10.1002/jsfa.2939
|View full text |Cite
|
Sign up to set email alerts
|

The influence of different single dietary sources on moult induction in laying hens

Abstract: An investigation was carried out to assess the possibility of using single dietary sources as alternatives to feed deprivation for the induction of moult in commercial laying hens. The study involved six dietary groups of 29 laying hens: unmoulted, dried tomato pomace, alfalfa meal, rice bran, cumin seed meal and feed withdrawal. The birds received the above diets during the moulting period (11 days), and body weight loss and ovary weight regression were measured. Post-moult production parameters (number of eg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
1
5
0
1
Order By: Relevance
“…Our results support the findings of others who reported that molted hens produce eggs with higher HU than do unmolted ones [42]. Mean premolt egg HU of 67.07 ± 1.74 increased for all treatment groups during the molt phase (Table 3 and Figure 1f).…”
Section: As Observed Insupporting
confidence: 95%
See 3 more Smart Citations
“…Our results support the findings of others who reported that molted hens produce eggs with higher HU than do unmolted ones [42]. Mean premolt egg HU of 67.07 ± 1.74 increased for all treatment groups during the molt phase (Table 3 and Figure 1f).…”
Section: As Observed Insupporting
confidence: 95%
“…Although hens in our study lost BW during the molt and regained it during postmolt, examination of the reproductive tracts was not performed. Mansoori et al [42] reported that feeding hens dried tomato pomace resulted in postmolt egg quality and egg production comparable with feed removal. The hens used in our study were most likely too old to show the type of enhanced production observed with the younger layers used by Mansoori et al [42].…”
Section: Production Performancementioning
confidence: 92%
See 2 more Smart Citations
“…Guar meal (10 and 15%) (Zimmerman et al, 1987), grape pomace with added thyroxin (Keshavarz and Quimby, 2002), various combinations of alfalfa (Landers et al, 2005;Donaldson 2005), and cottonseed meal (Davis et al, 2002) were also evaluated. Coconut meal and cumin seed meal were successfully used in layer and nonfeed-removal molt diets in Asian and Middle Eastern countries (Ravindran and Blaire, 1992;Mansoori 2007 …”
Section: Laying Hen and Poultry Feedstuffsmentioning
confidence: 99%